Argentina : Trade Patterns and Challenges Ahead - Anos-Casero, Paloma; Rollo, Valentina (2012)
Argentinean export growth was impressive during the recent economic boom (2003-2007). However, decomposing export growth reveals that the extensive margin (increases in exports of existing products to existing markets) dominates, while the intensive margin (increases in exports of new products or new markets) contributes little to export growth. Argentina's trade product concentration has increased in the past 10 years, and the main export products remain overwhelmingly natural-resource intensive. The little diversification of non-primary exports limits the country s ability to weather a decline in export commodity prices. The country has had some success finding new export markets, especially in Latin America, but should seek to develop deeper trade relationships with high GDP export destinations such as the European Union and the United States. Another challenge going forward is the relatively low sophistication of exports and limited integration into the global production chains, falling behind regional competitors such as Brazil. This calls for policy measures to improve the ability of existing firms to innovate and compete successfully in global markets.